Problem Analysis of the Use of Traditional Teaching Aids in Elementary School Physical Education Learning - M. Asri B (International Journal of Education, Culture, and Society, 2026)
Although the use of instructional media in physical education has received increasing attention in prior studies, research specifically examining the challenges of utilizing traditional teaching aids in elementary school physical education remains limited, particularly in rural settings. This study aims to analyze the problems encountered in the use of traditional teaching aids in physical education learning at SDN 49 Kabupaten Barru. A qualitative case study approach was employed involving 12 participants, comprising one physical education teacher and eleven students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using thematic analysis. The findings indicate that limited equipment availability (mean adequacy score = 2.1/5), lack of teacher training (reported in 78% of responses), and minimal institutional support significantly hinder the optimal implementation of traditional teaching aids. Observation results show that only 40% of planned traditional media activities were implemented effectively. Although student engagement during the use of traditional media reached 65%, it declined when equipment was incomplete. Thematic analysis identified four dominant challenges: infrastructure constraints, pedagogical limitations, low budget allocation, and shifting student preferences toward modern games. These results contribute to the theoretical development of culturally responsive pedagogy in physical education by demonstrating how contextual resource limitations shape instructional practice and student engagement. The study concludes that teacher competence and institutional support play a crucial role in optimizing the use of traditional teaching aids in rural elementary schools and recommends structured teacher training and adequate resource allocation to strengthen their implementation. Future research should experimentally test traditional media-based physical education models in broader and more diverse school contexts to further validate these findings.